Supplementation of L-Alanyl-L-Glutamine and Fish Oil Improves Body Composition and Quality of Life in Patients With Chronic Heart Failure. (November 2015) - Wu, Christina; Kato, Tomoko S.; Ji, Ruiping; Zizola, Cynthia; Brunjes, Danielle L.; Deng, Yue; Akashi, Hirokazu; Armstrong, Hilary F.; Kennel, Peter J.; Thomas, Tiffany; Forman, Daniel E.; Hall, Jennifer; et al.
Abstract : Background—: Skeletal muscle dysfunction and exercise intolerance are clinical hallmarks of patients with heart failure. These have been linked to a progressive catabolic state, skeletal muscle inflammation, and impaired oxidative metabolism. Previous studies suggest beneficial effects of ω-3 polyunsaturated fatty acids and glutamine on exercise performance and muscle protein balance. Methods and Results—: In a randomized double-blind, placebo-controlled trial, 31 patients with heart failure were randomized to either L-alanyl-L-glutamine (8 g/d) and polyunsaturated fatty acid (6.5 g/d) or placebo (safflower oil and milk powder) for 3 months. Cardiopulmonary exercise testing, dual-energy x-ray absorptiometry, 6-minute walk test, hand grip strength, functional muscle testing, echocardiography, and quality of life and lateral quadriceps muscle biopsy were performed at baseline and at follow-up. Oxidative capacity and metabolic gene expression were analyzed on muscle biopsies. No differences in muscle function, echocardiography, 6-minute walk test, or hand grip strength and a nonsignificant increase in peak VO2 in the treatment group were found. Lean body mass increased and quality of life improved in the active treatment group. Molecular analysis revealed no differences in muscle fiber composition, fiber cross-sectional area, gene expression of metabolic marker genes (PGC1α, CPT1, PDK4, and GLUT4), and skeletal muscle oxidative capacity. Conclusions—: The combined supplementation of L-alanyl-L-glutamine and polyunsaturated fatty acid did not improve exercise performance or muscle function but increased lean body mass and quality of life in patients with chronic stable heart failure. These findings suggest potentially beneficial effects of high-dose nutritional polyunsaturated fatty acids and amino acid supplementations in patients with chronic stable heart failure. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01534663. Abstract : Supplemental Digital Content is available in the text.